Contemporary review on spontaneous coronary artery dissection: insights into the angiographic finding and differential diagnosis - Kovacevic, M.; Jarakovic, M.; Milovancev, A.; Cankovic, M.; Petrovic, M.; Bjelobrk, M.; Ilic, A.; Srdanovic, I.; Tadic, S.; Dabovic, D.; Crnomarkovic, B.; Komazec, N.; et al. (Frontiers in Cardiovascular Medicine, 2023)
Spontaneous coronary artery dissection (SCAD), although in the majority of cases presents as an acute coronary syndrome (ACS), has different pathophysiology from atherosclerosis that influences specific angiography findings and enables most patients to be solved by optimal medical therapy rather than percutaneous coronary intervention (PCI).Therefore, accurate diagnosis is essential for adequate treatment of each patient as management of SCAD differs from that of ACS of atherosclerotic aetiology. So far, invasive coronary angiography remains the most important diagnostic tool in suspected SCAD.However, there are ambiguous cases that can mimic SCAD. In this review, the authors summarize current knowledge about the diagnostic algorithms, particularly angiographic features of SCAD, pitfalls of angiography, and the role of intracoronary imaging in the context of SCAD diagnosis. Finally, apart from the pathognomonic angiographic features of SCAD that are thoroughly discussed in this review, the authors focus on obscure angiography findings and findings that can mimic SCAD as well. Differential diagnosis and the timely recognition of SCAD are crucial as there are differences in the acute and long-term management of SCAD and other causes of ACS.